A comprehensive assessment of fractal wrinkling/eddy dissipation based combustion model for simulating conventional turbulent premixed and non-premixed flames. Issue 2 (23rd February 2021) - Farokhi, Mohammadreza; Birouk, Madjid
Abstract : This paper presents a step-forward extension of the well-known chemistry/flow interaction Eddy Dissipation Concept approach for modelling both, non-premixed and premixed, combustion regimes in a Reynolds-Averaged Navier Stokes framework. The Eddy Dissipation Concept approach and its extended versions (e.g. Partially Stirred reactors, PaSR) are widely used for CFD modelling of a variety of combustion systems. This is mainly due to their capability of incorporating chemical kinetic rates in turbulent flows. However, in defining the averaged chemical reaction rates, EDC describes the fine-scale of turbulent reacting flowfield based on the so-called mixing-rate calculated from turbulent velocity field, which consequently makes this model more suitable for diffusion flame/combustion regimes. In a recent study by the present authors, a hybrid Wrinkling-EDC approach is introduced to model fine scales of turbulent reacting flows in MILD combustion regimes based on flame surface density in premixed flame regimes and turbulent intermittency in diffusion flame regimes. In the present study, we study the performance of this newly developed approach for the simulation of conventional turbulent flames. The simulations are performed and validated using well-documented turbulent premixed and predominantly non-premixed flames (e.g. Flame F3 of Chen et al. and Sandia Flame D). In addition, all cases are simulated using a recently developed EDC model (referred to as extended EDC) along with the standard EDC version where both their results are used as a reference. The obtained results reveal better performance of the Wrinkling-EDC approach over the standard and extended versions of EDC model for the simulation of turbulent premixed flame, and a comparable performance between the extended EDC and wrinkling-EDC approach for the predictions of species concentration and temperature fields of turbulent non-premixed flames.